Optically pure D (-) lactic acid biosynthesis from diverse renewable biomass: microbial strain development and bioprocess analysis - Zhang, Yixing (Kansas State University, 2015)
Lactic acid is an important platform chemical that has long history and wide applications in food, polymer, pharmaceutics and cosmetic industries. Lactic acid has two optical isomers; namely D-lactic acid and L-lactic acid. Racemic mixture of lactic acid are usually used as preservatives and ingredients in solvents, or as precursors for different chemicals. Currently there is an increasing demand of optical pure lactic acid as a feedstock for the production of poly-lactic acid (PLA). PLA is a biodegradable, biocompatible and environmental friendly alternative to plastics derived from petroleum based chemicals. Optically pure D or L-lactic acid is used for the synthesis of poly D or L- lactic acid (PDLA, PLLA). Blend of PDLA with PLLA results in a heat-resistant stereocomplex PLA with excellent properties. As a consequence, large quantity of cost effective D-lactic acid is required to meet the demand of stereocomplex PLA. Lignocellulosic biomass is a promising feedstock for lactic acid production because of its availability, sustainability and cost effectiveness compared to refined sugars and cereal grain-based sugars. Commercial use of lignocellulosic biomass for economic production of lactic acid requires microorganisms that are capable of using all sugars derived from lignocellulosic biomass. Therefore, the objectives of this study were: 1) to produce high level of optically pure D-lactic acid from lignocellulosic biomass-derived sugars using a homofermentative strain L. delbrueckii via simultaneous saccharification and fermentation (SSF); 2) to develop a co-culture fermentation system to produce lactic acid from both pentose and hexose sugars derived from lignocellulosic biomass; 3) to produce D-lactic acid by genetically engineered L. plantarum NCIMB 8826 ∆ldhL1 and its derivatives; 4) to construct recombinant L. plantarum by introduction of a plasmid (pLEM415-xylAB) used for xylose assimilation and evaluate its ability to produce D-lactic acid from biomass sugars; and 5) to perform metabolic flux analysis of carbon flow in Lactobacillus strains used in our study. Our results showed that D-lactic acid yield from alkali-treated corn stover by L. delbrueckii and L. plantarum NCIMB 8826 ∆ldhL1 via SSF were 0.50 g g[superscript]-1 and 0.53 g g[superscript]-1 respectively; however, these two D-lactic acid producing strains cannot use xylose from hemicellulose. Complete sugar utilization was achieved by co-cultivation of L. plantarum ATCC 21028 and L. brevis ATCC 367, and lactic acid yield increased to 0.78 g g[superscript]-1 from alkali-treated corn stover, but this co-cultivation system produced racemic mixture of D and L lactic acid. Simultaneous utilization of hexose and pentose sugars derived from biomass was achieved by introduction of two plasmids pCU-PxylAB and pLEM415-xylAB carrying xylose assimilation genes into L. plantarum NCIMB 8826 ∆ldhL1, respectively; the resulting recombinant strains ∆ldhL1-pCU-PxylAB and ∆ldhL1-pLEM415-xylAB used xylose and glucose simultaneously and produced high yield of optically pure D-lactic acid. Metabolic flux analysis verified the pathways used in these Lactobacillus strains and provided critical information to judiciously select the desired Lactobacillus strain to produce lactic acid catering to the composition of raw material and the optical purity requirement. This innovative study demonstrated strategies for low-cost biotechnological production of tailor-made lactic acid from specific lignocellulosic biomass, and thereby provides a foundational manufacturing route for a flexible and sustainable biorefinery to cater to the fuel and chemical industry.
Keywords: Lactic acid; Lactobacilli; SSF; corn stover; fermentation; xylose assimilation; Agriculture, General (0473)